PENGARUH ANTARA PENDIDIKAN PENDAPATAN DAN PENGETAHUAN TENTANG KONSERVASI LAHAN TERHADAP PARTISIPASI PETANI DALAM KONSERVASI LAHAN DI KECAMATAN BULUKERTO KABUPATEN WONOGIRI TAHUN 2013 - nurhayati, siti (Pendidikan Geografi, 2013)
The purpose of this research is to : (1) Find out the influence of education toward land conservation understanding, (2) Find out the influence of income toward land conservation understanding, (3) Find out the influence of education toward farmers participation in land conservation, (4) Find out the influence of income toward farmers participation in land conservation, and (5) Find out the influence of land conservation understanding toward farmers participation in land conservation.  This research employs Correlational Survey method. The variables of this research are: education (X1), income (X2), land conservation understanding (X3), and farmers participation in land conservation (X4).  The population of this research are all farmers in Bulukerto Sub District. The sampling method used in this research are multistages and random sampling method. The data of this research were collected through interview and questionaires. The data were analyzed by applying statistical analysis of multiple linear regressive analysis and path analysis.The findings of this research are : (1) That there is significant direct influence between education and land conservation understanding, with amount of influential contribution of 7, 45 %. (2) That there is direct significant influence between income and land conservation understanding, with amount of influential contribution level of 7, 84 %. (3) That there is significant direct influence between education and farmers participation in land conservation, with amount of influential contribution of 7, 67 %. (4) That there is direct influence between income and farmers participation in land conservation with amount of influential contribution of 6, 2 %. (5) That there is significant direct influence between land cnservation understanding and farmers participation in land conservation, with amount of influential contribution of 10, 3 %. Path analysis also indicates that farmers education and income hold indirect influence through land conservation understanding toward farmers participation in land conservation in Bulukerto sub district.Key words       : Education, Income, Understanding, Participation, Land Conservation, Path   Analysis